Composite coatings of gellan gum and inulin with lactobacillus casei: enhancing the post-harvest quality of guava (2024)
Guava is a highly sought-after tropical fruit in the market due to its high content of vitamins, minerals, antioxidants, and other phenolic compounds. However, due to its climacteric nature, it has a short post-harvest shelf life. The aim of this study was to develop coatings based on gellan gum (GG) and inulin (IN) incorporating Lactobacillus casei, which were tested for their potential ability to extend the post-harvest shelf life of whole guava fruit. The coatings were prepared using the following formulations: 0.5 GG/1.0 IN (w/v), 0.8 GG/5.0 IN (w/v), 0.5 GG/1.0 IN(w/v), and 0.8 GG/5.0 IN (w/v). The coated and uncoated (control) fruits were stored at 25 °C for 12 days, and various quality attributes were evaluated (including respiration rate, soluble solids, titratable acidity, weight loss, total phenol content, and color). The results indicated that the application of the coatings reduced weight loss, color change, and respiration rate in the fruits. However, the 0.8 GG/5.0 IN (w/v) formulation provided the best maintenance of post-harvest quality for the fruit evaluated. The coatings with a higher inulin content showed the highest growth of L. casei, which could enhance the antimicrobial effect of the coating. Therefore, the combined application of L. casei and inulin in coatings based on gellan gum can be considered an effective treatment to extend the shelf life and preserve the quality of guava fruits.